2019
DOI: 10.4314/bcse.v33i3.2
|View full text |Cite
|
Sign up to set email alerts
|

Volatile profile of green coffee beans from Coffea arabica L. plants grown at different altitudes in Ethiopia

Abstract: This study was aimed to identify volatile compounds of 31 green coffee bean samples and evalute their correlation with altitude of the coffee plants grown in two zones (Gedeo and Jimma) in Ethiopia. A total of 81 different compounds were detected. The contents of dominant volatile compounds in green coffee beans were in the range: trans-linalooloxide (3.24⎯19.13%), linalool (1.56⎯21.76%), 2-methoxy-4-vinylphenol (2.34⎯15.08%) and cis-linalooloxide (1.03⎯13.27%). In addition, benzene acetaldehyde (0.45⎯10.97%),… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
20
0
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(21 citation statements)
references
References 35 publications
0
20
0
1
Order By: Relevance
“…Different analyses have shown that terpineol is the dominant alcohol in cold extracts among all alcohols [35]. It is difficult to compare the present result to other analyses as many of them only indicate the percentage of the respective compounds in the grain [78,82].…”
Section: Cyclic Aromatic Alcohols (Terpenes Derivative)mentioning
confidence: 78%
“…Different analyses have shown that terpineol is the dominant alcohol in cold extracts among all alcohols [35]. It is difficult to compare the present result to other analyses as many of them only indicate the percentage of the respective compounds in the grain [78,82].…”
Section: Cyclic Aromatic Alcohols (Terpenes Derivative)mentioning
confidence: 78%
“…These results are in agreement with previous research reporting the abundance of these chemicals in green coffee beans, i.e., alcohol, esters, hydrocarbons, and aldehydes [ 28 ]. Additionally, Tsegay et al [ 9 ] reported presence of chemical classes, i.e., furans, pyrazines, and pyridines, in green and roasted coffee. Our present work confirmed the finding, since we also observed these compounds (i.e., pyridine, furan, ketone, pyrazine, and pyrazole) in the green beans.…”
Section: Resultsmentioning
confidence: 99%
“…In this stage, Maillard reaction occurred as induced by heat exposure, producing melanoidin and heterocyclic components. Intriguingly, current studies revealed that both components contributed to formation of coffee flavor and antioxidant activity [ 8 , 9 ].…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, more recently, the right to the intellectual property of teff (Eragrosris tef) was also raised (Andersen & Winge, 2012;Simmonds et al, 2020). Consequently, protecting geographical origin necessitates Ethiopian specialty coffee because increased demand for specialty coffee in the international market dictates differentiating its origin (Giovannucci et al, 2008). It is necessary to implement intellectual property tools to ensure certification of single-origin coffee in producing countries.…”
Section: Critic Al Analys Is and Comparisonsmentioning
confidence: 99%